Perilaku Keuangan Generasi Z: Analisis Tantangan Akuntansi Pribadi Di Era Cashless Society - Rini Adriani Auliana; Fildana Listyani (PUBLIKASI RISETMAHASISWA AKUNTANSI, 2026)
Technological developments have changed the behavior of transactions and individual financial management, including Generation Z as the most active users of cashless services. Therefore, this study was conducted to analyze the challenges of implementing personal accounting in a cashless society and identify factors that influence the financial behavior of Generation Z. The study used a descriptive qualitative approach and literature study techniques through analysis of national and international scientific publications for the period 2020-2025. Sources were systematically selected from the Google Scholar, DOAJ, and Garuda databases with relevance to the themes of financial literacy, self-control, lifestyle, and financial technology. After data from each publication was extracted covering the main variables and study findings, the analysis was carried out using thematic analysis to identify patterns of relationships between concepts. In addition, the results of this study indicate that the ease of digital transactions significantly improves the situation of consumers who tend to be impulsive. However, financial literacy and self-control are dominant factors in efforts to maintain personal financial stability. The lack of daily financial recording and reporting practices leads to cash flow imbalances and significant dependence on irregular and irregular expressions. This study emphasizes the importance of developing personal accounting habits through recording transactions, preparing monthly budgets, and evaluating annual financial performance as a very appropriate strategy to promote healthy financial behavior among Generation Z.